A systemic functional analysis of LGBT characters in body 2 body: a Malaysian queer anthology - Tuani Ibrahim, Siti Muzlifah; Abdul Latiff, Muhamad Farid (Penerbit UMK, 2018)
This research investigates how authors in 19 short stories in the anthology, Body 2 Body: A Malaysian Queer Anthology (B2B) use language to portray LGBT characters. It also investigates if these authors reinforce or challenge the stereotypical views about LGBT people. The theoretical framework for this research is based on Systemic Functional Linguistics in which attitude is selected to examine the evaluation of LGBT characters. Based on the analysis, it reveals that authors in B2B have adopted various strategies to evaluate LGBT characters in their stories. The authors portray the LGBT character as insecure person. This results in these LGBT characters to be evaluated negatively. The stereotypical views about LGBT people are either reinforced or challenged mostly through the various tokens in affect and judgment. Finally, suggestions for future research are presented to strengthen linguistic analysis as a method to unravel authors‘ perspectives in literary texts.